2010
DOI: 10.1088/0004-637x/710/2/1063
|View full text |Cite
|
Sign up to set email alerts
|

New Limits on an Intermediate-Mass Black Hole in Omega Centauri. Ii. Dynamical Models

Abstract: We present a detailed dynamical analysis of the projected density and kinematical data available for the globular cluster ω Centauri. We solve the spherical anisotropic Jeans equation for a given density profile to predict the projected profiles of the RMS velocityσ(R), in each of the three orthogonal coordinate directions (line of sight, proper motion radial, and proper motion tangential). The models allow for the presence of a central dark mass, such as a possible intermediate-mass black hole (IMBH). We fit … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
87
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 196 publications
(96 citation statements)
references
References 83 publications
7
87
0
2
Order By: Relevance
“…7 for example shows that their isotropic no-IMBH model is already in very good agreement with the observed velocity dispersion profile, while it provides a very poor fit in our case. It is therefore not clear if the inclusion of radial anisotropy would change the velocity dispersion profile by a large enough amount to bring our models without IMBHs into agreement with the observations, especially since van der Marel & Anderson (2010) and the proper motion data of Watkins et al show that ω Cen is essentially isotropic in its center and only mildly radially anisotropic beyond 200 arcsec. It seems more likely that ω Cen contains either a dark cluster of compact remnants or a population of low-mass stars in its center on top of what mass segregation is already producing in our models, or a ∼ 40,000 M⊙ IMBH.…”
Section: Intermediate-mass Black Holesmentioning
confidence: 74%
See 2 more Smart Citations
“…7 for example shows that their isotropic no-IMBH model is already in very good agreement with the observed velocity dispersion profile, while it provides a very poor fit in our case. It is therefore not clear if the inclusion of radial anisotropy would change the velocity dispersion profile by a large enough amount to bring our models without IMBHs into agreement with the observations, especially since van der Marel & Anderson (2010) and the proper motion data of Watkins et al show that ω Cen is essentially isotropic in its center and only mildly radially anisotropic beyond 200 arcsec. It seems more likely that ω Cen contains either a dark cluster of compact remnants or a population of low-mass stars in its center on top of what mass segregation is already producing in our models, or a ∼ 40,000 M⊙ IMBH.…”
Section: Intermediate-mass Black Holesmentioning
confidence: 74%
“…Noyola et al (2010) and Jalali et al (2012) reported evidence for a 50000 M⊙ IMBH in the globular cluster ω Cen based on VLT-FLAMES integrated spectra of the central parts of the cluster and detailed N -body models. In contrast, van der Marel & Anderson (2010) found that the velocity dispersion increase in the center can be explained by a radially anisotropic velocity dispersion profile and derived a 1σ upper limit of only 12000 M⊙ for any possible IMBH.…”
Section: Intermediate-mass Black Holesmentioning
confidence: 92%
See 1 more Smart Citation
“…These most massive clusters also tend to show a wider range of stellar ages and chemical compositions than is seen in typical globular clusters, suggesting that they were formed gradually rather than as a single unit. The three prominent stripped galaxy candidates that are in our own local neighbourhood all show dynamical evidence for a central 10 4 M } black hole [90][91][92] , although the detections are still controversial 93 . Radiation from these putative black holes has not yet been detected 75,94 .…”
Section: Future Prospectsmentioning
confidence: 88%
“…Internal rotation may also play an indirect role in the open question of whether there are intermediate-mass black holes (IMBH) in some GCs. In fact, the detection of strong gradients in the velocity dispersion profile toward the cluster core is often interpreted as a hint of the presence of an IMBH (Baumgardt et al 2005), but the evidence gathered so far in support of the existence of IMBHs is inconclusive and controversial, and none of the published studies (van der Marel & Anderson 2010;Lützgendorf et al 2011;Lanzoni et al 2013) did consider differential rotation, which, together with anisotropy, can yield gradients in the velocity dispersion profiles Bianchini et al 2013). Finally, recent investigations indicate that rotation could be a key ingredient in the formation of multiple generations of stars in GCs (Bekki 2010;Mastrobuono-Battisti & Perets 2013).…”
Section: Introductionmentioning
confidence: 99%